Iron load and redox stress in skeletal muscle of aged rats. - Altun, M; Edström, E; Spooner, E; Flores-Moralez, A; Bergman, E; Tollet-Egnell, P; Norstedt, G; Kessler, B; Ulfhake, B (2007)
Loss of skeletal muscle mass (sarcopenia) is a major contributor to disability in old age. We used two-dimensional gel electrophoresis and mass spectrometry to screen for changes in proteins, and cDNA profiling to assess transcriptional regulations in the gastrocnemius muscle of adult (4 months) and aged (30 months) male Sprague-Dawley rats. Thirty-five proteins were differentially expressed in aged muscle. Proteins and mRNA transcripts involved in redox homeostasis and iron load were increased, representing novel components that were previously not associated with sarcopenia. Tissue iron levels were elevated in senescence, paralleling an increase in transferrin. Proteins involved in redox homeostasis showed a complex pattern of changes with increased SOD1 and decreased SOD2. These results suggest that an elevated iron load is a significant component of sarcopenia with the potential to be exploited clinically, and that mitochondria of aged striated muscle may be more vulnerable to radicals produced in cell respiration.